Identification of chemosensitizing agents of colorectal cancer in Rauvolfia vomitoria using an NMR-based chemometric approach - Cui, Wei-Liang; Guo, Dong-Xiao; Wang, Ning; Wang, Zhi-Fan; Ji, Jian-Bo; Wang, Xiao; Yang, Chun-Guo; Lin, Yong-Qiang; Wang, Shu-Qi (Frontiers in Chemistry, 2023)
Searching for new adjuvants of conventional chemotherapeutic approaches against colorectal cancer cells is extremely urgent. In current research, a non-targeted analytical approach was established by combining proton nuclear magnetic resonance spectroscopy with a chemometrics data mining tool to identify chemosensitizing agents from Rauvolfia vomitoria. This approach enabled the identification of potential active constituents in the initial fractionation process and provided their structural information. This strategy was validated by its application to Rauvolfia vomitoria extract exhibiting chemosensitizing activity on 5-fluorouracil against colorectal cancer cells. After the workflow, the biochemometrics analysis showed that at least 15 signals (Variable influence on projection (VIP) > 1) could have contributions in the differentiation of various fractions. Through systematic literature and database searches, we found that the most active fraction (fraction 7) exhibited the highest presence of sabazin-type and armaniline-type alkaloids, which were potential chemosensitizers as previously reported. To validate the results of the strategy, the effect of 5-FU and compounds isolated from fraction 7 incubation on HCT-8 and LoVo cell vialibilty were evaluated. These results evidenced that compound β-carboline (3), 1-methyl-β-carboline (4), and lochnerine (6) could enhance the cytotoxicity of 5-fluorouracil against to CRC cells. Besides, 21 compounds including two new compounds were isolated from Rauvolfia vomitoria. The experimental results verify the reliability of the method, and this approach provides a new and efficient tool to overcome some of the bottlenecks in natural products drug discovery.